2021
DOI: 10.3389/fpls.2021.625138
|View full text |Cite
|
Sign up to set email alerts
|

Target-Site and Non-target-Site Resistance Mechanisms Confer Multiple and Cross- Resistance to ALS and ACCase Inhibiting Herbicides in Lolium rigidum From Spain

Abstract: Lolium rigidum is one the worst herbicide resistant (HR) weeds worldwide due to its proneness to evolve multiple and cross resistance to several sites of action (SoA). In winter cereals crops in Spain, resistance to acetolactate synthase (ALS)- and acetyl-CoA carboxylase (ACCase)-inhibiting herbicides has become widespread, with farmers having to rely on pre-emergence herbicides over the last two decades to maintain weed control. Recently, lack of control with very long-chain fatty acid synthesis (VLCFAS)-inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 30 publications
2
58
0
Order By: Relevance
“…Crop selectivity to several chloroacetamide herbicides and safeners is mediated by enhanced GST activity, as a result of increased GST expression (Leavitt and Penner, 1979;Lamoureux and Rusness, 1989;Frova, 2006;Riechers et al, 2010). Enhanced amount of GSTF1 protein, a biomarker of NTST was found in L. rigidum population that showed reduced sensitivity to VLCFA inhibitors Torra et al (2021). Thus far, resistance to VLCFA inhibitors in weedy species is attributed to NTSR mechanism mediated by enhanced GST activity (Busi et al, 2018;Brabham et al, 2019;DĂŒcker et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Crop selectivity to several chloroacetamide herbicides and safeners is mediated by enhanced GST activity, as a result of increased GST expression (Leavitt and Penner, 1979;Lamoureux and Rusness, 1989;Frova, 2006;Riechers et al, 2010). Enhanced amount of GSTF1 protein, a biomarker of NTST was found in L. rigidum population that showed reduced sensitivity to VLCFA inhibitors Torra et al (2021). Thus far, resistance to VLCFA inhibitors in weedy species is attributed to NTSR mechanism mediated by enhanced GST activity (Busi et al, 2018;Brabham et al, 2019;DĂŒcker et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Metsulfuron-methyl is widely known for its low use doses, high efficacy and crop selectivity, and broad-spectrum in controlling many broadleaf and grass weeds [ 29 ]. Resistance to Metsulfuron-methyl has been reported in several monocotyledonous weeds, such as Lolium rigidum [ 21 , 30 ], Avena fatua [ 12 ], and Polypogon fugax [ 31 ]. In this study, the four R, kamoji populations showed no symptoms after being treated with metsulfuron-methyl at recommended field dose.…”
Section: Discussionmentioning
confidence: 99%
“…To date, at least 29 amino acid substitutions have been identified at eight sites [ 13 , 14 , 15 , 16 , 17 ]. However, the non-target-site resistance (NTSR) mechanism, endowed by the metabolism of ALS inhibitors by key enzymatic complexes such as glutathione S -transferases (GST) and cytochrome P450 monooxygenases (CytP450), was also identified in some weed species [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in wheat growing areas in Europe the widespread presence of Acetyl CoA Carboxylase inhibitors (ACCase-inhibitors) resistant grass weeds, such as Lolium spp., has forced farmers to replace the once-predominant herbicides with Acetolactate Synthase inhibitors (ALS-inhibitors). However, after a few years of reliance on these latter herbicides, resistance has evolved also against ALS-inhibitors and weeds with multiple resistance are now common (Loureiro et al, 2017, Torra et al, 2021. Farmers then adopt other classes of herbicides to support or replace those that have reduced efficacy due to the evolution of herbicide resistance, entering in a continuous process of new herbicide use or combining new herbicides that can be referred to as a "herbicide treadmill" following the concept of the "pesticide treadmill" (Foster and Magdoff, 2000).…”
Section: Herbicide Resistancementioning
confidence: 99%